Stress relaxation test for monitoring post mortem textural changes of ice-stored cod (Gadus morhua L.) - Herrero, Ana M.; Heia, K.; Careche, Mercedes (Journal of Food Science, 2004)
The possibilities of using the stress relaxation test as a nondestructive method to monitor post-mortem textural changes of ice-stored cod have been evaluated. The stress relaxation tests were performed in gutted cod. Fish were compressed by 5% and deformation was kept constant for 60 s. The relaxation curves obtained were fitted to nonlinear and linear regression models. Nonlinear regressions with 2 or 3 exponential terms and the linear regression model could be fitted to the relaxation curve of ice-stored cod, although the three-terms exponential models gave the best results for assessing the quality of ice-stored cod (maximum relative difference ≤ 2% and R2 > 0.999). The highest differences were found between pre-rigor and in-rigor states. Peer Reviewed